Distribution of causes of abnormal uterine bleeding using new FIGO classification system-PALM COEIN: a rural tertiary hospital based study - Betha, Kalpana; Malavatu, Lavanya; Talasani, Sreeveena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal Uterine Bleeding (AUB) is a significant debilitating clinical condition. It may have a significant impact on women’s quality of life with significant burden to the country’s economy. The primary aim was to categorize women with Abnormal Uterine Bleeding (AUB) according to PALM COEIN classification system and to correlate the clinical diagnosis and histopathologic features of various causes of AUB. Methods: A retrospective study was carried out on 250 non-gravid reproductive age women between 25-45 years with complaints of AUB at Mediciti Institute of Medical Sciences, a rural tertiary teaching hospital during the period January 2014 to December 2015. Results: The PALM and COEIN groups accounted for 60.4% and 39.6% respectively. Leiomyoma was the most common cause of AUB (30.4%) and Ovulatory disorders was the 2nd most common cause of AUB (13.6%). A total of 172 (68.8%) were classified as having chronic AUB and 78(31.2%) as having acute AUB. In AUB-L, the difference in clinical and histopathological diagnosis was significant (p=0.03). Conclusions: Structural causes of AUB contributed more to the cause of AUB. The PALM COEIN classification system helps us in understanding various etiological causes of AUB and can be used by clinicians and researchers for international comparisons.